The invisible worm: ovarian cancer. (4th June 2009) - Reeve, Gill; Mackay-Thomas, Stuart
Abstract : It took nine months for her GP practice to diagnose Gill Reeve's symptoms as ovarian cancer. She wants to know why it took so long.